Correlation Study of Body Mass Index with Blood Pressure, Blood Uric Acid Levels, and Blood Sugar Levels - Darsini, Darsini; Cahyono, Eko Agus (Universitas Islam Lamongan, 2024)
The increase in the number of people who have an excess body mass index has an important impact on health problems and reduced quality of life. Excessive body mass index has been identified as a trigger factor for hypertension, hyperuria, type 2 diabetes mellitus, and several other types of diseases. The research design used was analytical with a cross sectional approach. The sample in this study was 181 respondents who were selected using purposive sampling. The variables in this study are body mass index, blood pressure, uric acid levels in the blood and blood sugar levels. The data collection instrument used in this research was an observation sheet. The data analysis test was carried out using the Spearman rho rank test. From the results of data analysis using the Spearman Rho rank correlation test, it was found that there was a correlation between body mass index and blood pressure (p value: 0.014 and r: 0.183), there was a correlation between body mass index and uric acid levels in the blood (p value: 0.028 and r: 0.164), and there is a correlation between body mass index and blood sugar levels (p value: 0.005 and r: 0.209). An increase in body mass index experienced by a person will trigger an increase in blood pressure, uric acid levels in the blood and blood sugar levels. Implementing a healthy lifestyle by doing regular physical activity, limiting eating patterns and consuming healthy foods, managing stress and avoiding various factors that trigger an increase in body mass index will help a person to avoid several types of chronic diseases